Roving Workshop Approach to CSA & CSV Scaling - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
IIRR first facilitated roving workshop approach for CCAFS CSV teams; it was adopted as an annual learning event for CCAFS. IIRR used the approach in training 16 DA regional teams and local governments in Philippines and NGOs in Myanmar and Laos. SEARCA has adopted the approach in training ASEAN-CRN.